Emulation of an ELISA Reader and Quantitative Image Analysis Using the Computer Program Digital-OD - Stephan Jansen; Bernd Kriegesmann; Bertram Brenig (BioTechniques)
Here, we present a Microsoft® Windows® application that has been written to emulate a microplate reader. After scanning a standard 96-well microplate, color gradations in the slots can be analyzed quantitatively and be used for the estimation of enzyme kinetics, binding assays or concentration determination. In a test, series accuracy of the program was determined. We show that the returned optical densities correlated highly with the true concentrations (r > 0.97). Thus, the software is useful for a wide number of applications. Further, the program is easy to handle and is available free of charge.